2021
DOI: 10.1186/s12888-021-03249-4
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic traits in young people and how experiencing shame relates to current attachment challenges

Abstract: Background Young people with pathological narcissistic traits may have more maladaptive ways of relating to themselves and others. In this study, we investigated how the experience of shame may be a mechanism by which vulnerable and grandiose pathological narcissism relates to negative and positive internalised models of the self and others, manifested as attachment styles. Methods Participants (N = 348) were young people who reported on pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 104 publications
3
7
0
Order By: Relevance
“…Conversely, vulnerable narcissism was negatively related to attachment styles denoting a positive model of self -dismissive and secure attachment. This result indicates that these attachment styles may be of particular relevance to the study of vulnerable pathological narcissism, and extends previous findings (e.g., Dickinson and Pincus, 2003;Smolewska and Dion, 2005;Fossati et al, 2015;Zhang et al, 2017b;van Schie et al, 2021). Furthermore, vulnerability was found to be associated with negative trait emotional reactivity, and results examining change in affect from baseline indicated that the experience of rejection was especially salient, negative and intense for those high in pathological narcissistic vulnerability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Conversely, vulnerable narcissism was negatively related to attachment styles denoting a positive model of self -dismissive and secure attachment. This result indicates that these attachment styles may be of particular relevance to the study of vulnerable pathological narcissism, and extends previous findings (e.g., Dickinson and Pincus, 2003;Smolewska and Dion, 2005;Fossati et al, 2015;Zhang et al, 2017b;van Schie et al, 2021). Furthermore, vulnerability was found to be associated with negative trait emotional reactivity, and results examining change in affect from baseline indicated that the experience of rejection was especially salient, negative and intense for those high in pathological narcissistic vulnerability.…”
Section: Discussionsupporting
confidence: 86%
“…Measurement of attachment styles on one hand, and pathological narcissism on the other, has varied widely between studies, creating challenges when comparing results. However, findings of recent research utilizing the PNI (Pincus et al, 2009) and Bartholomew and Horowitz's (1991) attachment model indicated that vulnerable pathological narcissism was positively related to both fearful and preoccupied attachment and negatively related to security in attachment, with this relationship mediated by feelings of shame (van Schie et al, 2021). In contrast, grandiose narcissism was positively related to secure attachment, but was unrelated to any of the three insecure attachment styles.…”
Section: Pathological Narcissism and Adult Attachment Stylesmentioning
confidence: 81%
“…Albert’s affective experience is essentially characterized by feelings of grandiosity and inadequacy, accompanied by helplessness, loneliness, shame and humiliation, and hypersensitivity to criticism [ 71 ]. The pervasive anxiety regarding threats to the self negatively influences the quality of his interpersonal relationships [ 72 ]. Indeed, as highlighted by the PDC-A (MA Axis), Albert’s capacity to engage in stable, intimate, and satisfying relationships is one of the most “damaged”.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also show narcissism contributing to diminished COVID-19 prevention behaviour ( Nowak et al, 2020 ; Zajenkowski et al, 2020 ). Grandiose narcissists may think they are too important to adhere to restrictions, and anxiety and neuroticism might drive COVID-19 prevention behaviour in non-resilient and shameful vulnerable narcissists ( Sękowski et al, 2021 ) who avoid criticism ( van Schie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%